Molecular dynamics simulation of stretching-force-induced H-type RNA pseudoknot unfolding - Seah, Yi Ling (2016)
Ribonucleic acids have a wide-range of spatial structures to accommodate its diverse biological functions. The most prevalent tertiary structure is the hairpin-type pseudoknot, which is an essential downstream stimulatory element for minus-one ribosomal frameshifting. Minus-one ribosomal frameshifting is a translational recoding mechanism widely used by RNA viruses and eukaryotes to maintain a fixed ratio of gene products. While the mechanical stability and frameshifting efficiency of these downstream messenger RNA pseudoknots were tested in optical tweezer experiments, in silico studies were limited. Here, molecular dynamics simulation will be carried out to unfold delta U177 pseudoknot of human telomerase RNA. Microscopic molecular structures and dynamic processes, which cannot be observed in optical tweezer experiments, will be illustrated. Both molecular dynamics simulations and optical tweezer experiments revealed that the delta U177 pseudoknot can unfold using three types of pathways. Furthermore, mechanical unfolding of the mutant native pseudoknot showed that less force was required due to UUUAA-to-CCCGU mutation-induced destabilization. Hence, pseudoknot stability is strongly dependent on these major-groove (UUU) and minor groove (AA) stem-loop interactions. Given that frameshifting efficiency is highest in wild-type pseudoknot, anti-viral therapeutics against frameshifting may be developed based on these three-dimensional structures.